Measuring distance from the incisors to the esophageal cancer by FDG PET/CT: endoscopy as the reference - Szu-Wei Hsu; Jeffrey S. Chang; Wei-Lun Chang; Forn-Chia Lin; Nan-Tsing Chiu (BMC Gastroenterology, 2022)
Abstract Background Using endoscopy as the reference, this study evaluated the accuracy of 18F-fluorodeoxyglucose positron emission tomography/computed tomography (FDG PET/CT) in measuring distance from the incisors to the PET detectable esophageal cancer. If there is high concordance between endoscopic and PET measurements, our results may provide a basis to use FDG PET/CT in cooperation with endoscopic measurement to localize those PET/CT and CT undetectable esophageal tumors for radiotherapy planning. Materials Esophageal cancer patients with pretreatment endoscopy and FDG PET/CT detectable esophageal tumors were recruited retrospectively. The distances from the incisors to the proximal esophageal tumor margins were determined by endoscopy and by the sagittal images of FDG PET/CT. The endoscopic measurement was used as the comparative reference. A nuclear medicine doctor and a radiation oncologist each performed the FDG PET/CT measurement twice for every patient. We analyzed the differences in these measurements, and assessed agreement and reproducibility of the results by the intraclass correlation coefficient (ICC). Results Thirty-four patients, with 35 esophageal tumors, were included. By endoscopy and FDG PET/CT, the mean distances from the incisors to the proximal esophageal tumor margin were 27.3 ± 6.4 cm (range 17.1–40.0 cm) and 26.8 ± 6.3 cm (range 15.7–41.3 cm), respectively. The mean absolute differences between the endoscopic and four FDG PET/CT measurements ranged from 1.129 to 1.289 cm (SD: 0.98–1.19). The measurement agreement between FDG PET/CT and endoscopy by ICC was between 0.962 and 0.971. The intra- and interobserver reproducibilities of the two readers were excellent (intraobserver ICC: 0.985, 0.996; interobserver ICC: 0.976–0.984). Conclusions FDG PET/CT was in high agreement with endoscopy in measuring the distance from the incisors to the proximal esophageal tumor margin. For FDG PET/CT and CT undetectable esophageal cancer, incorporation of the endoscopic measurement with PET/CT might be a way for making radiotherapy plan.